Visual Content Design Strategy of the @binarmusik Instagram Account in Increasing Views and Audience Engagement - Ogya Mahadana Yoganta; Rahina Nugrahani; Mohd Ekram Al Hafis bin Hashim (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
This study analyzes the content strategy of the Instagram account @binarmusik in increasing audience engagement through visual design, messaging, and content segmentation using a descriptive qualitative approach and content analysis of posts and account insights. The findings show that each content segment plays a distinct role, where informative content achieves higher reach, narrative and comparative content encourages comments, and curated content drives saving behavior. Visual elements such as color, typography, and layout help attract attention and improve readability, while message structure through hooks, informative captions, and calls to action enhances interaction. Overall, audience engagement is multidimensional and influenced by content characteristics, indicating that an integrated strategy combining visual elements, messaging, and segmentation effectively increases engagement on social media.